Wooded trail with boarded walk and railing at Ayun Mapu - Unknown:::Creator::::::::::::
Photograph shows a trail running through the redwoods at the YWCA's Camp Ayun Mapu in Big Basin, California. Part of the trail is a boarded walk with a railing.